Critical appraisal, evidence-based medicine and scientific divulgation during the pandemic related to COVID-19 in Brazil (Revista de Estudios Brasileños, 2023)
The objective of this text is to reflect on the role of the dissemination of scientific evidence and evidence-based medicine in the context of the COVID-19-related pandemic in Brazil; and the need to rethink our teaching in light of these reflections. One of the aspects in which there was huge disagreement regarding public messages was related to non-pharmacological measures and treatment. The wide availability of information democratizes knowledge, but also generates the need for scientific literacy of the general population and health professionals for an adequate selection and critical appraisal of the evidence, since the multiplicity of messages about ways to deal with the epidemic possibly contributed to the difficulty of control in Brazil.